Assessment of Autism Symptoms During the Neonatal Period: Is There Early Evidence of Autism Risk? - Pineda, Roberta (Am J Occup Ther, 2015)
OBJECTIVE. To define neonatal social characteristics related to autism risk. METHOD. Sixty-two preterm infants underwent neonatal neurobehavioral testing. At age 2 yr, participants were assessed with the Modified Checklist for Autism in Toddlers and Bayley Scales of Infant and Toddler Development, 3rd edition. RESULTS. Positive autism screening was associated with absence of gaze aversion, χ = 5.90, p =.01, odds ratio = 5.05, and absence of endpoint nystagmus, χ = 4.78, p = .02, odds ratio = 8.47. Demonstrating gaze aversion was related to better language outcomes, t(55) = −3.07, p ≤ .003. Displaying endpoint nystagmus was related to better language outcomes, t(61) = −3.06, p = .003, cognitive outcomes, t(63) = −5.04, p < .001, and motor outcomes, t(62) = −2.82, p = .006. CONCLUSION. Atypical social interactions were not observed among infants who later screened positive for autism. Instead, the presence of gaze aversion and endpoint nystagmus was related to better developmental outcomes. Understanding early behaviors associated with autism may enable early identification and lead to timely therapy activation to improve function.